Comparison of Face-to-face and Distance Education Based on Incremental Self-theory in terms of Students’ Academic Achievement, Self-confidence, and Motivation and Teacher Views - Orhan, Sema İrem; Aydın, Abdullah (Kastamonu Egitim Dergisi, 2025)
Purpose: This study aimed to compare the effects of implementing activities and materials designed according to incremental self-theory in face-to-face and distance education teaching the cell and divisions unit in the 7th-grade science lesson on students’ academic achievement, self-confidence, and motivation. Another aim is to gather the science teacher’s views about the implementation process. Design/Methodology/Approach: In the research, a sequential explanatory design, which is a type of mixed research method in which quantitative and qualitative research methods are used together, was used. Findings: As a result of the research, significant differences were found in favor of the students who received face-to-face education in terms of academic achievement levels, and the students who received distance education in terms of motivation levels. There was no significant difference between the two groups regarding self-confidence levels. The teachers, also, stated that the designed education positively affected students’ morale, and motivation toward the lesson. Highlights: Within the scope of the research, it may be helpful to integrate the teaching process, which is designed in line with the incremental self-theory and does not interfere with the curriculum of any lesson, into other lessons and subjects where students have learning problems and low motivation.
Keywords: Incremental self-theory; Face-to-face education; Distance education; Science lesson; Science Education; Fen Bilgisi Eğitimi